PENGARUH PELATIHAN LADDER DRILL 90 DEGREE ROTATION DAN LADDER DRILL ALI SHUFFLE TERHADAP PENINGKATAN DAYA LEDAK OTOT TUNGKAI DAN KECEPATAN - Pelamonia, Shandy Pieter; Harmono, Bayu Akbar (JP.JOK (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2018)
Physical condition is a very important component in sports activities while they are achievement or learning. Explosive power leg muscle and speed of motion is the dominant component in sporting activities such as basketball, soccer, volleyball, martial art. The purpose of this study was to determinate This research is a